Understanding the C4 dicarboxylic acid metabolism in Clostridium autoethanogenum - Breitkopf, Ronja (2018)
The acetogenic bacterium Clostridium autoethanogenum possesses the inherent ability to produce acetate and ethanol during growth on industrial waste gases such as carbon monoxide and carbon dioxide using the Wood-Ljungdahl Pathway (WLP) for carbon fixation. With the urgent need to reduce greenhouse gas emissions and produce chemicals and fuels in a more sustainable manner, autotrophic organisms such as C. autoethanogenum have received considerable industrial interest over recent years. However, the metabolic pathways present in C. autoethanogenum and therefore its capability to produce industrial relevant carbon building-blocks and biofuels have not yet been sufficiently examined. Therefore, the investigation of pathways leading to the production of industrially relevant carbon building blocks is seen as a worthwhile undertaking at the interface of fundamental and applied research. In this project, the metabolism of C4 dicarboxylic acids in C. autoethanogenum in conjunction with the production of succinate was investigated. This analysis revealed a previously unrecognised carbon and energy source, fumarate, and unveiled the combination of the autotrophic WLP with reactions of the branched tricarboxylic acid (TCA), Krebs “cycle” using in vivo NMR techniques. Under the conditions employed, the reducing equivalents gained from the oxidative breakdown of fumarate to acetate were used to partially re-assimilate the CO2 that was liberated during that process. Accordingly, inactivation of the fumarate hydratase led to a disruption of fumarate metabolism. Additionally, through the introduction of a fumarate reductase and its overexpression in the organism, the resulting strain was able to produce succinate in amounts of up to 3.54 g l-1 and yields of up to 0.78 g g-1 fumarate. This study therefore presents an essential basis for the possible establishment of succinate production with C. autoethanogenum and a better understanding of its C4 dicarboxylic acid metabolism.